Factors associated with sexual behaviours among adolescents in a rural Tanzania: evidence from the African Research, Implementation Science, and Education (ARISE) Network - Elihuruma Eliufoo Stephano; Mussa Hassan Bago; Tian Yusheng; Jacktan Josephat Ruhighira; Mtoro J. Mtoro; Azan Abubakar Nyundo; Li Yamin (Discover Public Health)
Abstract Background Rural adolescents are now reaching adulthood earlier than in previous generations, resulting in a rise in unsafe sexual behaviours. These adolescents face more significant challenges than their urban counterparts, including limited access to healthcare, lower contraceptive use, and reduced sexual education. Rural areas are hard to reach due to infrastructure and cultural barriers, which exacerbate these sexual health disparities. The purpose of this study is to examine factors associated with sexual behaviours among adolescents in rural Tanzania. Methods This study utilises data from the African Research, Implementation Science, and Education (ARISE) Network’s Adolescent Health Study, a cross-sectional study in six countries in sub-Saharan Africa involving rural adolescents aged 10–19 years. Data on participant demographics, health, and sexual behaviours were collected through an interview-administered questionnaire. Univariate and multivariate Poisson regression analyses were conducted on key variables using STATA 18. These analyses were used to assess the factors associated with ever having had sex. Data were collected between July 2015 and December 2017. Results A total of 1,226 adolescents were enrolled. The proportion of adolescents who had ever had sex was 21.1% (95% CI 18.9–23.5). Of those, 45.6% reported having more than one sexual partner. Being female was inversely associated with ever having sexual intercourse (APR 0.37; 95% CI 0.29–0.47). Age was significantly associated with ever had sex (APR 1.17; 95% CI 1.12–1.23). Living with a colleague (APR 2.92; 95% CI 1.96–436), adolescents who have been employed within the past year (APR 1.34; 95% CI 1.09–1.65), being exposed to pornography (APR 2.07; 95% CI 1.64–2.60) and receiving a sex joke, (APR 1.84; 95% CI 1.51–2.24) were significantly associated with ever had sex among adolescents. Conclusion The findings highlight factors impacting sexual behaviour among adolescents. Promoting adolescents’ sexual health and well-being requires community-based interventions, family involvement, and comprehensive sexual education programs. Efforts must be made to raise public understanding of good sexual practice behaviour.